Politik gaya Sengkuni dan estetika Semar kajian antropologi sastra terhadap pemilu legislatif - Suwardi Endraswara (Masyarakat, Kebudayaan dan Politik, 2014)
This article aims to explain two unique political actions, namely Sengkuni style and Seamr aesthetic. Both styles were viewed from litterature anthropology perspective. This methapor provides authentic data from 2009 election, expected to be a reflection the 2014 election. The study shows that politic, culture, and litterature were conected to each other, produces methapor in two political style. First, in this transitional era, sengkuni style is more favorable in targetting people, especially the middle class-men. Secondly is semar aesthetic style, more suitable for upper class-men group, those who hold their tradition tightly. This style suits better to pro-people type of leader. In conclusion, researcher found that both style has its strength and weakness, mostly depends on the targetted group in the community.